GUIDELINES FOR THE DEVELOPMENT OF DIGITAL LEADERSHIP ACCORDING TO THE 4 PRINCIPLES OF BHAVANA OF THE ADMINISTRATORS OF EDUCATIONAL OPPORTUNITY EXPANSION SCHOOLS UNDER OFFICE OF CHONBURI EDUCATIONAL SERVICE AREA 2 - Worasayan, Phusanisa; Phrakhruphattharathammakhun; Thitavaddhano, Phramaha Yannawat (Journal of Educational Review Faculty of Education in MCU, 2022)
The objectives of this research paper were 1) to study the state of leadership in the digital age of school administrators to expand educational opportunities; 2) to study the guidelines for the development of leadership in the digital age of Bhavana IV by school administrators to expand educational opportunities in elementary, and 3) to propose guidelines for developing leadership in the digital age according to Bhavana IV of school administrators to expand educational opportunities Chonburi Primary Educational Service Area Office 2 is an integrated research method, namely 1) quantitative research, using a questionnaire, a sample group of 234 teachers of the Opportunity Expansion School was used. The data were analyzed by statistics such as frequency, percentage, mean, standard deviation, and 2) qualitative research. Conducted interviews with 7 key informants. Data were analyzed by content analysis. Results of the research showed that 1) the digital era leadership of school administrators expanded educational opportunities. Office of Chonburi Primary Educational Service Area 2, in overall and in each aspect, it was found that the level of practice was at a high level. 2) Guidelines for developing leadership in the digital era according to Bhavana IV of school administrators to expand educational opportunities in elementary school. It is the development of leadership in the digital age in 5 aspects by integrating Bhavana IV which is the Dharma principles that are suitable for the development of administrators, namely Kayabhavana, Silabhavana, Cittabhavana, and Panyabhavana. 3) Guidelines for developing leadership in the digital era according to Bhavana IV principles of School administrators expand educational opportunities, Chonburi Primary Educational Service Area Office 2 consisted of 1) Visionary leadership as a role model for others, making them look and see as an example; 2) Leadership in change is courageous and open, dare to face the truth Pioneers encourage innovation in schools; 3) Information technology leadership is a role model in the use of information technology and communication with social responsibility; 4) Inspirational leadership is a role model for self-domination, people domination, and dominate the job; 5) Support leadership is the one who keeps the spirit of the team alive in continuous operation.